iNkolimahashi Shelter: the excavation of Later Stone Age rock shelter deposits in the central Thukela Basin, KwaZulu-Natal, South Africa - Mazel, A. D. (Southern African Humanities, 2016)
In this paper, I present the results of the excavation of iNkolimahashi Shelter in the central Thukela Basin. The site was inhabited primarily by hunter-gatherers, but I propose that Layers 1 and 2, which date to within the last 360 years, relate to the occupation of the site by agriculturists. The 550 b.p. deposits contain a mix of remains that suggest occupation by both hunter-gatherers and agriculturists. The iNkolimahashi dates confirm the conclusion reached with the excavation of kwaThwaleyakhe, that the central Thukela Basin was occupied by Holocene hunter-gatherers before 2000 b.p. It would appear that the site was first occupied around 4000 years ago. The absence of pottery in the iNkolimahashi 1990 b.p. deposits has compelled me to question the timing of the introduction of pottery into the Thukela Basin. I reconsider conclusions reached previously that pottery was introduced into the Thukela Basin before 2000 years ago.